2009
DOI: 10.1186/1471-2202-10-136
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged rote learning produces delayed memory facilitation and metabolic changes in the hippocampus of the ageing human brain

Abstract: BackgroundRepeated rehearsal is one method by which verbal material may be transferred from short- to long-term memory. We hypothesised that extended engagement of memory structures through prolonged rehearsal would result in enhanced efficacy of recall and also of brain structures implicated in new learning. Twenty-four normal participants aged 55-70 (mean = 60.1) engaged in six weeks of rote learning, during which they learned 500 words per week every week (prose, poetry etc.). An extensive battery of memory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 52 publications
0
10
0
3
Order By: Relevance
“…1 H MRS has been widely used to investigate developmental neurobiology in mammalian brains (Larvaron et al, 2006; Tkac et al, 2003; Weiss et al, 2009). Recently, 1 H MRS technique has been employed to study the metabolite profiles for measuring neuroplasticity in response to environmental stimuli or injury (Bernabeu et al, 2009; Pajonk et al, 2010; Roche et al, 2009; Singh et al, 2009). In the present study, 1 H MRS at 7 T has been shown to reveal early biochemical or metabolic changes in visual cortex in neonatal ME model.…”
Section: Discussionmentioning
confidence: 99%
“…1 H MRS has been widely used to investigate developmental neurobiology in mammalian brains (Larvaron et al, 2006; Tkac et al, 2003; Weiss et al, 2009). Recently, 1 H MRS technique has been employed to study the metabolite profiles for measuring neuroplasticity in response to environmental stimuli or injury (Bernabeu et al, 2009; Pajonk et al, 2010; Roche et al, 2009; Singh et al, 2009). In the present study, 1 H MRS at 7 T has been shown to reveal early biochemical or metabolic changes in visual cortex in neonatal ME model.…”
Section: Discussionmentioning
confidence: 99%
“…The subcortical structures that have been associated with the processing of emotional memories are the Prefrontal Cortex, Amygdala, Anterior Cingluate Cortex, Hippocampus, and the Insula [5]. However, within these structures, the hippocampus and amygdala have been the most studied structures that were found to process emotions related to memory encoding, thus processing and storing them in the long term memory system [6,7]. To take emotional memory processing a bit more further, a journal article by William James (1884) entitled "What is an Emotion" brought into perspective one of the most thought provoking questions about emotions and how they can possibly be related to memory encoding.…”
Section: Brief Backgroundmentioning
confidence: 99%
“…To take emotional memory processing a bit more further, a journal article by William James (1884) entitled "What is an Emotion" brought into perspective one of the most thought provoking questions about emotions and how they can possibly be related to memory encoding. James proposed an innovative theory whereby human emotions occurred in response to afferent feedback loops from the sensory receptors in the skin, muscles, cartilage, and other organs which produced physical changes alongside the emotional experience [7].…”
Section: Brief Backgroundmentioning
confidence: 99%
“…A aprendizagem mecânica, apesar de apresentar um tempo de retenção menor, ativa uma rede neural complexa e distribuída em diversas áreas encefálicas, como córtex pré-frontal inferior esquerdo, área motora suplementar, córtex parietal posterior bilateral, cerebelo lateral e lobo temporal medial, incluindo o hipocampo (ROCHE et al, 2009). Levando em consideração estas afirmações, parece provável que muitas informações provenientes da aprendizagem mecânica ficam retidas na memória de curto prazo e na memória de trabalho.…”
Section: Neurociência E Aprendizagem Significativa: é Possível Uma Inunclassified